Effects of High-Lipid Dietary Protein Ratio on Growth, Antioxidant Parameters, Histological Structure, and Expression of Antioxidant- and Immune-Related Genes of Hybrid Grouper - Weibin Huang; Hao Liu; Shipei Yang; Menglong Zhou; Shuang Zhang; Beiping Tan; Yuanzhi Yang; Haitao Zhang; Ruitao Xie; Xiaohui Dong (Animals, 2023)
The hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus) is a new species of grouper crossed from giant grouper (E. lanceolatus) as the male parent and brown-marbled grouper (E. fuscoguttatus) as the female parent. We hypothesized that optimal levels of dietary protein may benefit liver function. High-lipid diets are energetic feeds that conserve protein and reduce costs, and are a hot topic in aquaculture today. Therefore, the objective of the research is to investigated the effects of dietary protein level in high-lipid diets on serum and liver biochemistry, liver histology, and liver immune and antioxidant indexes and gene mRNA expression of the juvenile hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus). Six iso-lipidic (161 g/kg) diets were formulated containing graded levels of protein (510 as control, 480,450, 420, 390 and 360 g/kg). Each treatment consisted of three replicates and 30 fish (6.70 ± 0.02 g) in one replicate. After an 8-week feeding experiment, the results indicated the following: (1) With the decreasing of dietary protein level, the specific growth rate (SGR) of groupers increased gradually and then decreased; SGRs of the 390 and 360 g/kg groups were significantly lower than other groups (p < 0.05). (2) In terms of serum and liver, the activity of antioxidant enzymes such as catalase (CAT) and superoxide dismutase (SOD), and the total antioxidant capacity (T-AOC) content, and the activity of immune enzymes such as lysozyme (LYS) and immunoglobulin (IgM) was significantly increased under the appropriate protein level. (3) Based on liver histology, we know that high or low dietary protein levels cause liver damage. (4) Dietary protein levels can significantly affect the mRNA expression levels of an anti-inflammatory factor gene (tgfβ), pro-inflammatory factor genes (il6, il8), heat shock proteins, and antioxidant and immune genes (hsp70 and hsp90, gpx, nrf2, keap1). It is concluded that the appropriate protein level can promote the growth performance of groupers, improve antioxidant activity and immune enzyme activity in serum and liver, and enhance the expression of immune genes.